Appeal for Help for the International Brigade
034-0081-002 APPEAL FOR HELP FOR THE INTERNATIONAL BRIGADE All great causes have always brought forward self sacrifices. In old time, men went to help weak and oppressed people. As in the past, La Fayette went to help the American people, as Garibaldi or Bolivar, as the volunteers for the freedom of Greece, or as Villebois-Mareuil, Colonel of the French Army, going to help the Boers, or as Armand Carel who in 1823, went to Spain, to fight at the head of a French squadron, against king Ferdinand VII who intended to crush his own subjects who wanted freedom, we have just seen the glorious history of the International Brigades. The world never saw such a great and beautiful thing. Following the example of their predecessors, those volunteers of liberty crossed the Pyrenees without asking anything from anybody, those men coming from 52 countries, gave their wives and children into our care. They set out to win Peace in their homes and ours, they started for us. They left behind them, in Madrid, Guadalajara, Jarrama [Jarama], in Aragon, Estremadure or Catalogne [Catalonia], 5,000 of them, in that land watered with their generous blood. They followed the tragic destiny of Spain. They have now been forced to return to the french frontier, and have been enclosed in camps and left destitute. These men did not deserve such a fate. They have nothing except solidarity that already has done much and will do still more. Wilst the brave volunteers of America, Canada, England, France, Sweden and Belgium have been welcomed back enthusiastically by huge crowds their comrades wait on the frontier amongst the and snow of the Pyrenees. Help us to guarantie that each one shall reach his home if his security is not menaced by the destroyers of liberty and human dignity. Help us to find for these heroes a shelter and a peaceful land. The countries which welcome them can rely on them. They are fine men whose past life is vouched for by the lack of ambition, which led them to a sacrifice which will never be forgotten. Help us to find the necessary money for the execution of this plan. The whole of humanity must watch over these men as its own sons. Mmes Genevieve TABIOUS Ecrivain Andrée VIOLLYS Ecrivain Madeleine JACOB Ecrivain Elaine BRAULI Ecrivain Andrée MARTY-CAPGRAS Professor MM. Méd. Général PELOQUIN - Colonel NYCOLETIS - Lt.Col VINCENT - Lt .Col. BIENFAIT Pierre COT Député- ancien Ministre Aimé COTTON President de l'Académie des Sciences FORCINAL Député President du Groupe Parlementaire Lucien VOGEL Editeur 292/946/34/81(ii)